Contemporary Discourses in Social Exclusion - Alemanji, Aminkeng A.; Meijer, Clara Marlijn; Kwazema, Martins; Benyah, Francis Ethelbert Kwabena (Springer International Publishing, 2022)
1. Introduction -- PART 1: SEXUALITY, RACE AND SOCIAL EXCLUSION -- 2. Doing Sensitive Research on Stigma, Sexuality and Religion: The Use of Q-Methodology. Clara Marlijn Meijer -- 3. When Whiteness and muscles are all that matter. Gay dating apps as spaces of exclusion, perspectives from Britain, Roy Celaire -- 4. Inclusive Dreams and Excluded Realities: An Analysis and Critique of ‘Xenophobic’ Rhetoric, and Practices of Exclusion in the South African ‘Rainbow Nation,’ Khushal Naik and Åbo Akademi -- 5. Intra-Racism: The Token Blackie?, Runyararo Sihle Chivaura -- PART 2: IDENTITY POLITICS, RELIGION, AND SOCIAL EXCLUSION -- 6. SOCIAL EXCLUSION AS REFLECTIONS OF PAST-FUTURES: THEORIZING AN ONTOLOGICAL STARTING POINT FOR UNDERSTANDING SOCIAL EXCLUSION, Martins Kwazema -- 7. The Occult, Popular Culture, and the Politics of Hope in the Ghanaian Entertainment Industry Seth Tweneboah -- 8. Interfaith coexistence or social exclusion? Milena Parland -- 9. Daring to be different in an androcentric world: The critical reflections on a Muslim woman in Ghana. By Charles Prempeh -- 10. Are Albinos People like Us?: Albinism and Social Exclusion in Ghana. Francis Benyah -- 11. Migration and questions of governance, equality and discrimination in the Finnish context. Nora Repo-Saeed -- 12. Australians trying to return home: Alienation, a cause and effect during the Covid-19 era?, Alexander Rehnberg -- 13. One and free? A Wittgensteinian Analysis of the Change to the Words of the Australian National Anthem Ryan Manhire.